Ethnic Values - Revival of Attributes of Nomad Life in Education of Descendants - Bozorova Muslima Kodirovna (Researchparks Publishing, 2022)
The author reflects on the issues of educating the younger generation with the history of his native land, explaining the influence of the past on today, the impact of the nomadic lifestyle forms its own, different from the settled customs and traditions, social institutions and institutions, moral, religious and legal norms, way of thinking and mentality , their cultural forms and